Is the Interplay between Epigenetic Markers Related to the Acclimation of Cork Oak Plants to High Temperatures? - Correia, Barbara; Valledor, Luis; Meijón, Mónica; Rodriguez, José Luis; Dias, Maria Celeste; Santos, Conceição; Cañal, Maria Jesus; Rodriguez, Roberto; Pinto, Glória (PLoS ONE, 2013)
Trees necessarily experience changes in temperature, requiring efficient short-term strategies that become crucial in environmental change adaptability. DNA methylation and histone posttranslational modifications have been shown to play a key role in both epigenetic control and plant functional status under stress by controlling the functional state of chromatin and gene expression. Cork oak (Quercus suber L.) is a key stone of the Mediterranean region, growing at temperatures of 45°C. This species was subjected to a cumulative temperature increase from 25°C to 55°C under laboratory conditions in order to test the hypothesis that epigenetic code is related to heat stress tolerance. Electrolyte leakage increased after 35°C, but all plants survived to 55°C. DNA methylation and acetylated histone H3 (AcH3) levels were monitored by HPCE (high performance capillary electrophoresis), MS-RAPD (methylation-sensitive random-amplified polymorphic DNA) and Protein Gel Blot analysis and the spatial distribution of the modifications was assessed using a confocal microscope. DNA methylation analysed by HPCE revealed an increase at 55°C, while MS-RAPD results pointed to dynamic methylation-demethylation patterns over stress. Protein Gel Blot showed the abundance index of AcH3 decreasing from 25°C to 45°C. The immunohistochemical detection of 5-mC (5-methyl-2′-deoxycytidine) and AcH3 came upon the previous results. These results indicate that epigenetic mechanisms such as DNA methylation and histone H3 acetylation have opposite and particular dynamics that can be crucial for the stepwise establishment of this species into such high stress (55°C), allowing its acclimation and survival. This is the first report that assesses epigenetic regulation in order to investigate heat tolerance in forest trees.
The following values have no corresponding Zotero field: publisher: Public Library of Science accession-num: 23326451
Keywords: Acclimatization; Acclimatization: genetics; Acetylation; Blotting; CHROMATIN; CORK oak (citation; Deoxycytidine; Deoxycytidine: analogs & derivatives; Deoxycytidine: metabolism; DNA; DNA methylation; Electrolytes; Electrolytes: metabolism; Epigenesis; Gene expression; Genetic; Genetic Markers; Genome; Heat-Shock Response; Heat-Shock Response: genetics; Histones; Histones: metabolism; Physiological; Physiological: genetics; Plant; Plant Leaves; Plant Leaves: metabolism; Plant: genetics; POST-translational modification; Quercus; Quercus: genetics; Quercus: physiology; Random Amplified Polymorphic DNA Technique; Stress; tags); Temperature; TREES -- Research; Western

Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galvàn, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of Proteome Research, 2013)
Responses to drought stress by water withholding have been studied in 1 year old Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) seedlings from seven provenances from Andalusia (southern Spain). Several physiological parameters, including predawn xylem water potentials and relative water content in soil, roots, and leaves as well as maximum quantum efficiency and yield of PSII were evaluated for 28 days in both irrigated and nonirrigated seedlings. The leaf proteome map of the two provenances that show the extreme responses (Seville, GSE, is the most susceptible, while Almer??a, SSA, is the least susceptible) was obtained. Statistically significant variable spots among provenances and treatments were subjected to MALDI-TOF/TOF-MS/MS analysis for protein identification. In response to drought stress, ?12.4% of the reproducible spots varied significantly depending on the treatment and the population. These variable proteins were mainly chloroplastic and belonged to the metabolism and defense/stress functional categories. The 2-DE protein profile of nonirrigated seedlings was similar in both provenances. Physiological and proteomics data were generally in good agreement. The general trend was a decrease in protein abundance upon water withholding in both provenances, mainly in those involved in ATP synthesis and photosynthesis. This decrease, moreover, was most marked in the most susceptible population compared with the less susceptible one.
From Duplicate 2 (Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galván, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V)
Keywords: Analysis of Variance; biomass; Chlorophyll ﬂuorescence; drought stress in Holm oak; Droughts; Electrophoresis; Gel; Gene Expression Regulation; Holm oak proteomics; Physiological; Physiological: genetics; Physiological: physiology; Plant; Plant Leaves; Plant Leaves: genetics; Plant Leaves: metabolism; Plant Proteins; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: genetics; Quercus: metabolism; Quercus: physiology; Seedling; Seedling: growth & development; Seedling: metabolism; Spain; Stress; Tandem mass spectrometry; Two-Dimensional; water potential

QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia (Plant Physiology and Biochemistry, 2013)
Abstract Cork oak is an economically important forest species showing a great tolerance to high temperatures and shortage of water. However, the mechanisms underlying this plasticity are still poorly understood. Among the stress regulators, transcription factors (TFs) are especially important since they can control a wide range of stress-inducible genes, which make them powerful targets for genetic engineering of stress tolerance. Here we evaluated the influence of increasing temperatures (up to 55 °C) or drought (18% field capacity, FC) on the expression profile of an R2R3-MYB transcription factor of cork oak, the QsMYB1. QsMYB1 was previously identified as being preferentially expressed in cork tissues and as having an associated alternative splicing mechanism, which results in two different transcripts (QsMYB1.1 and QsMYB1.2). Expression analysis by reverse transcription quantitative PCR (RT-qPCR) revealed that increasing temperatures led to a gradual down-regulation of QsMYB1 transcripts with more effect on QsMYB1.1 abundance. On the other hand, under drought condition, expression of QsMYB1 variants, mainly the QsMYB1.2, was transiently up-regulated shortly after the stress imposition. Recovery from each stress has also resulted in a differential response by both QsMYB1 transcripts. Several physiological and biochemical parameters (plant water status, chlorophyll fluorescence, lipid peroxidation and proline content) were determined in order to monitor the plant performance under stress and recovery. In conclusion, this report provides the first evidence that QsMYB1 TF may have a putative function in the regulatory network of cork oak response to heat and drought stresses and during plant recovery.
From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 24161757
Keywords: Abiotic stress; Adaptation; Cork oak; Droughts; Gene expression; Gene Expression Regulation; Genes; Hot Temperature; Physiological; Plant; Plant Bark; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; Recovery; RNA Splicing; Stress; Transcription Factors; Transcription Factors: genetics; Transcription Factors: metabolism; water

Characterization of radial bending properties of cork - Anjos, Ofélia; Pereira, Helena; Rosa, Maria Emília (European Journal of Wood and Wood Products, 2011)
The behaviour of cork under three point bending stress in the radial direction was evaluated in relation to porosity (range 2.0–15.4%) and density (range 0.160– 0.220 g cm−3 ). The study was made using water-boiled cork planks of two commercial quality classes (good and poor quality) collected at an industrial mill. Cork samples were cut with the largest dimension in two directions, axial and tangential, and with the load zone in the inner part and the outer part of the plank. The stress-strain curves obtained in bending were similar for the different test specimens and similar to those observed for tensile tests in cork but the mechanical resistance of cork in bending was higher than in tension and lower than in compression. The direction of the internal stress in samples submitted to bending was a highly signiﬁcant factor of variation. The curves showed an initial linear elastic region with a mean Young’s modulus of 14 MPa for the tangential direction and 21 MPa for the axial direction, followed by a region of a gradual cork yielding up to a peak load, and failure at an average stress of 1.2 MPa and a strain of 14%. There was signiﬁcant difference in the bending properties of cork samples obtained from cork planks of different quality classes. Density and porosity were not individually well correlated with the mechanical parameters. It was however possible to model Young’s modulus by combining porosity and density.
Keywords: Bending; Compression; Cork; Density (voyant); Fracture; Quality; Stress

Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Penuelas, Josep; Lope-Piedrafita, Silvia (BMC plant biology, 2010)
Drought is a common stressor in many regions of the world and current climatic global circulation models predict further increases in warming and drought in the coming decades in several of these regions, such as the Mediterranean basin. The changes in leaf water content, distribution and dynamics in plant tissues under different soil water availabilities are not well known. In order to fill this gap, in the present report we describe our study withholding the irrigation of the seedlings of Quercus ilex, the dominant tree species in the evergreen forests of many areas of the Mediterranean Basin. We have monitored the gradual changes in water content in the different leaf areas, in vivo and non-invasively, by 1H magnetic resonance imaging (MRI) using proton density weighted (rhow) images and spin-spin relaxation time (T2) maps.
From Duplicate 1 ( Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Peñuelas, Josep; Lope-Piedrafita, Silvia )
Keywords: Droughts; Magnetic Resonance Imaging; Physiological; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus: metabolism; Seedling; Seedling: metabolism; Soil; Soil: analysis; Stress; Time Factors; water; Water: metabolism (citation)

Tensile properties of cork in axial stress and influence of porosity, density, quality and radial position in the plank - Anjos, Ofélia; Pereira, Helena; Rosa, M. Emília (European Journal of Wood and Wood Products, 2010)
The behaviour of cork under tensile stress in the axial direction was studied for samples taken from cork planks of good (class 1) and poor (class 4) quality grades and at three radial positions within the plank (inner, mid and outer positions). The effect of cork density (ranging from 0.123 to 0.203 g cm−3 ) and porosity (ranging from 2.8 to 9.6% in the tangential surface) on Young’s modulus and fracture stress and strain was studied. The tensile stress-strain curves of cork showed an elastic deformation up to 2% strain with a Young’s modulus of 30.8 MPa, and a fracture stress of 1.05 MPa at a strain of 7.1% for class 1, and Young’s modulus of 26.1 MPa, and a fracture stress of 0.77 MPa at a strain of 5.5% for class 4. Fracture always started at a pore. The quality class and the radial position in the plank were highly signiﬁcant factors of the tensile properties variation with good quality cork in the inner part of the plank showing the highest strength. Density inﬂuenced the elastic behaviour of cork with a highly signiﬁcant correlation of increasing E with density,but not so clearly the fracture stress and strain. The variability of tensile properties with porosity was large and although signiﬁcant, the correlations were lower in spite of a decreasing trend of E with porosity. Fracture depended on the type of defects in cork.
Keywords: Cork; Density; Porosity (voyant); Quality; Stress; Tensile

Plasticity and stress tolerance override local adaptation in the responses of Mediterranean holm oak seedlings to drought and cold - Gimeno, Teresa E; Pías, Beatriz; Lemos-Filho, José P; Valladares, Fernando (Tree Physiology, 2009)
Plant populations of widely distributed species experience a broad range of environmental conditions that can be faced by phenotypic plasticity or ecotypic differentiation and local adaptation. The strategy chosen will determine a population’s ability to respond to climate change. To explore this, we grew Quercus ilex (L.) seedlings from acorns collected at six selected populations from climatically contrasting localities and evaluated their response to drought and late season cold events. Maximum photosynthetic rate (Amax), instantaneous water use efficiency (iWUE), and thermal tolerance to freeze and heat (estimated from chlorophyll fluorescence versus temperature curves) were measured in 5-month-old seedlings in control (no stress), drought (water-stressed), and cold (low suboptimal temperature) conditions. The observed responses were similar for the six populations: drought decreased Amax and increased iWUE, and cold reduced Amax and iWUE. All the seedlings maintained photosynthetic activity under adverse conditions (drought and cold), and rapidly increased their iWUE by closing stomata when exposed to drought. Heat and freeze tolerances were similarly high for seedlings from all the populations, and they were significantly increased by drought and cold, respectively; and were positively related to each other. Differences in seedling performance across populations were primarily induced by maternal effects mediated by seed size and to a lesser extent by idiosyncratic physiologic responses to drought and low temperatures. Tolerance to multiple stresses together with the capacity to physiologically acclimate to heat waves and cold snaps may allow Q. ilex to cope with the increasingly stressful conditions imposed by climate change. Lack of evidence of physiologic seedling adaptation to local climate may reflect opposing selection pressures to complex, multidimensional environmental conditions operating within the distribution range of this species.
10.1093/treephys/tpn007
Keywords: Adaptation; Biological; Biological: physiology; Cold Temperature; Droughts; eﬃciency; Freezing; Genetic Variation; Hot Temperature; Nuts; photosynthesis; Photosynthesis: physiology; Physiological; Quercus; Quercus ilex; Quercus: physiology; Stress; thermal tolerance; Trees; water; water use; Water: physiology

Effects of sulphurous gases in two CO2 springs on total sulphur and thiols in acorns and oak seedlings - Grill, D; Müller, M; Tausz, M; Strnad, B; Wonisch, A; Raschi, A (Atmospheric Environment, 2004)
Quercus ilex and Quercus pubescens acorns were collected at two CO2 springs in Tuscany (Bossoleto and Viterbo, resp.). In addition to elevated CO2, these springs are a source of H2S and SO2 . Acorns from a comparable ﬁeld site distant from CO2 springs were used as controls. Acorns from CO2 springs contained signiﬁcantly higher sulphur concentrations than controls (0.67 vs. 0.47 mg g 1 dw in Q. ilex cotyledons and 1.01 vs. 0.80 in Q. pubescens) and, in Q. ilex, also more glutathione (1634 vs. 1393 nmol g 1 dw). When acorns were germinated and seedlings grown under ambient air conditions in the Botanical Garden in Graz for one year, leaves of Q. pubescens grown from CO2 spring acorns showed signiﬁcantly higher S-concentrations than leaves grown from control acorns (2.27 mg g 1 vs. 1.56 mg g 1 dw), and those of Q. ilex higher glutathione concentrations (929 vs. 462 nmol g 1 dw, CO2 spring vs. control acorns). One-year-old Q. ilex seedlings grown from CO2 spring acorns also showed elevated rates of chromosomal aberrations in root tips (a widely used test for environmental impacts), suggesting a permanent stress situation of the seedlings originating from the CO2 springs.
Keywords: cytogenetic; Glutathione; hydrogen sulphide; Stress; Sulphur dioxide

USE OF THERMAL IMAGING TECHNIQUES AND XANTHOPHYLLS CONTENT FOR DETERMINATION OF STRESS IN CORK OAK (QUERCUS SUBER L.) - Tronina, L; Grant, O M; Ramalho, J C; Chaves, M M (ACTA PHYSIOLOGIAE PLANTARUM, 2004)
Understanding the responses of cork oak (Quercus suber L.) to actual and predicted summer conditions is essential to determine the future sustainability of cork oak woodlands in Iberia. Thermal imaging may provide a rapid method for monitoring the extent of stress. The ecophysiology of cork trees was studied over three years. Three treatments were applied by means of rainfall capture and irrigation, with plots receiving 120%, 100%, or 80% of natural precipitation. Despite stomatal closure, detected using both thermal imaging and porometry, leaf water potential fell during the summer, most drastically during the third year of accumulative stress. The quantum efficiency (ΦPSII) and the maximum efficiency Formula of photosystem II also fell more intensely over the third summer, while non-photochemical quenching (NPQ) increased. The reduced precipitation treatment sporadically further reduced leaf water potential, stomatal conductance (gs), IG (an index of gs derived from thermal imaging), ΦPSII, and Formula, and increased leaf temperature and NPQ. It is concluded that these are very resilient trees since they were only severely affected in the third year of severe drought (the third year registering 45% less rainfall than average), and removing 20% of rainfall had a limited impact.
Key words: AS
Keywords: Quercus suber L.; Stress; thermal imaging

USE OF THERMAL IMAGING TECHNIQUES AND XANTHOPHYLLS CONTENT FOR DETERMINATION OF STRESS IN CORK OAK (QUERCUS SUBER L.) - Tronina, L.; Grant, O. M.; Ramalho, J. C.; Chaves, M. M. (ACTA PHYSIOLOGIAE PLANTARUM, 2004)
Understanding the responses of cork oak (Quercus suber L.) to actual and predicted summer conditions is essential to determine the future sustainability of cork oak woodlands in Iberia. Thermal imaging may provide a rapid method for monitoring the extent of stress. The ecophysiology of cork trees was studied over three years. Three treatments were applied by means of rainfall capture and irrigation, with plots receiving 120%, 100%, or 80% of natural precipitation. Despite stomatal closure, detected using both thermal imaging and porometry, leaf water potential fell during the summer, most drastically during the third year of accumulative stress. The quantum efficiency (ΦPSII) and the maximum efficiency Formula of photosystem II also fell more intensely over the third summer, while non-photochemical quenching (NPQ) increased. The reduced precipitation treatment sporadically further reduced leaf water potential, stomatal conductance (gs), IG (an index of gs derived from thermal imaging), ΦPSII, and Formula, and increased leaf temperature and NPQ. It is concluded that these are very resilient trees since they were only severely affected in the third year of severe drought (the third year registering 45% less rainfall than average), and removing 20% of rainfall had a limited impact.
Key words: ASKey words: ASThe following values have no corresponding Zotero field: pub-location: TIERGARTENSTRASSE 17, D-69121 HEIDELBERG, GERMANY publisher: SPRINGER HEIDELBERG
Keywords: Quercus suber L.; Stress; thermal imaging

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M. M.; Pereira, J. S.; MAROCO, J.; Rodrigues, M. L.; RICARDO, C. P. P.; OSÓRIO, M. L.; CARVALHO, I.; FARIA, T.; PINHEIRO, C. (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf10510.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M M; Pereira, J S; MAROCO, J; RODRIGUES, M L; RICARDO, C P P; OSÓRIO, M L; CARVALHO, I; Faria, T; PINHEIRO, C (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

Embriogénesis gamética para obtención de haploides en alcornoque. - Bueno, A; GÓMEZ, A; Boscaiu, M; Manzanera, J A; Vicente, O (II Congreso Forestal Español, 1997)
Inducción of haploid embryos and regeneration of plantlets have been obtained for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by culture at 25°C in a simple agar medium without growth regulator.s. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytic development of the microspores and for the induction of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; Haploid plants; Stress

Embriogénesis gamética para obtención de haploides en alcornoque. - Bueno, A.; GÓMEZ, A.; Boscaiu, M.; Manzanera, J. A.; Vicente, O. (II Congreso Forestal Español, 1997)
Inducción of haploid embryos and regeneration of plantlets have been obtained for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by culture at 25°C in a simple agar medium without growth regulator.s. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytic development of the microspores and for the induction of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that like most forest trees, are still recalcitrant in anther culture.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: anther culture; Cork oak; Haploid plants; Stress

Stress-induced formation of haploid plants through anther culture in cork oak (Quercus suber) - Bueno, Maria Angeles; Gomez, Arancha; Boscaiu, Monica; Manzanera, Jose Antonio; Vicente, Oscar (Physiologia Plantarum, 1997)
Induetion of haploid embryos and regeneration of plantlets have been obtained, for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by eulture at 25°C in a simple agar medium without growth regulators. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of' several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytie development of the mierospores and for the induetion of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that, like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; flow cytometry; Haploid plants; heat shock; Quercus suber; starvation; Stress

Stress-induced formation of haploid plants through anther culture in cork oak (Quercus suber) - Bueno, Maria Angeles; Gomez, Arancha; Boscaiu, Monica; Manzanera, Jose Antonio; Vicente, Oscar (Physiologia Plantarum, 1997)
Induetion of haploid embryos and regeneration of plantlets have been obtained, for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by eulture at 25°C in a simple agar medium without growth regulators. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of' several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytie development of the mierospores and for the induetion of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that, like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; flow cytometry; Haploid plants; heat shock; Quercus suber; starvation; Stress